2009
DOI: 10.1021/ja807723p
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Targeting Using Protein-Functionalized Micelles: The Strength of Multiple Weak Interactions

Abstract: Collagen is an important marker for the assessment of tissue remodeling, both in normal tissue maturation and in a variety of prevalent disease processes. Given the importance of multivalency in the natural interactions of collagen, multivalent ligands provide unique opportunities to target collagen architectures. Here, we explored the use of micelles as dynamic self-assembling multivalent scaffolds for the collagen binding protein CNA35. Despite the increased popularity of micelles as nanosized carriers in ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
41
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 56 publications
(113 reference statements)
5
41
2
2
Order By: Relevance
“…Figure S5). The more important ligand-receptor interaction observed with CKAAKN-functionalized nanoparticles, as compared with the free peptide, demonstrated that the affinity of phage-display-derivated peptides can be significantly enhanced thanks to the multivalent interactions offered by a scaffold-like nanosized material in concordance with previous observations [33,34]. Although peptides present several advantages in comparison to other targeting homing devices (i.e., easy of synthesis and low immunogenicity), they usually possess modest target affinity.…”
Section: Ligand-receptor Interactionsupporting
confidence: 84%
See 1 more Smart Citation
“…Figure S5). The more important ligand-receptor interaction observed with CKAAKN-functionalized nanoparticles, as compared with the free peptide, demonstrated that the affinity of phage-display-derivated peptides can be significantly enhanced thanks to the multivalent interactions offered by a scaffold-like nanosized material in concordance with previous observations [33,34]. Although peptides present several advantages in comparison to other targeting homing devices (i.e., easy of synthesis and low immunogenicity), they usually possess modest target affinity.…”
Section: Ligand-receptor Interactionsupporting
confidence: 84%
“…Although peptides present several advantages in comparison to other targeting homing devices (i.e., easy of synthesis and low immunogenicity), they usually possess modest target affinity. However, the conjugation of multiple copies of targeting ligand onto the nanocarrier surface, allows overcoming this limitation by enabling multivalent interaction with high binding constants and improving targeting efficacy [33]. These results allowed identifying the biological target of the CKAAKN peptide confirming also its surface localization.…”
Section: Ligand-receptor Interactionmentioning
confidence: 97%
“…In one approach peptide phage display was used to identify linear 7-mer peptides with a moderate affinity for collagen type I. 25 Multivalent display of this peptide on a pentavalent dendritic AB 5 scaffold was shown to successfully mimic the multivalent architecture of the peptides displayed on the original phage, resulting in a 100-fold increase in collagen affinity. Another demonstration of the potency of multivalent interactions was provided by a second study that used micelles and liposomes as multivalent scaffolds for the collagen binding protein CNA35.…”
Section: Introductionmentioning
confidence: 99%
“…Another demonstration of the potency of multivalent interactions was provided by a second study that used micelles and liposomes as multivalent scaffolds for the collagen binding protein CNA35. 14,25 This well-characterized collagen binding protein binds various types of collagen with a K d of 0.5 lM by wrapping around the collagen triple helix 26 and was shown to be a useful probe to monitor collagen formation in tissue engineering and in atherosclerotic plaques. 27 decrease the dissociation rate of these micelles in surface plasmon resonance binding (SPR) studies, being stable for more than 8 h under conditions of continuous flow.…”
Section: Introductionmentioning
confidence: 99%
“…[8,[21][22][23][24] Collagen contains a high density of CNA35 binding sites, allowing fluorescent imaging of collagen without the need to remove non-bound CNA35. [21,23] Here we report circularization of CNA35 as a new approach to generate a dual-specific collagen-targeting probe that only binds collagen after activation by MMP1.…”
mentioning
confidence: 99%